V-shaped plot at intersection of Mahapalika Marg and DN Road - Ghosh, Ayan (Jio Institute, 2023)
Bombay Municipal Corporation commissioned Frederick W. Stevens to design a new building to hold its offices. The site offered was a V-shaped plot opposite Chhatrapati Shivaji Maharaj Terminus (CSMT, formerly Victoria Terminus) at the intersection of Mahapalika Marg (formerly Cruikshank Road) and Dadabhai Naoroji Road (formerly Hornby Road).